Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13568-020-0962-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some flavonoids on the mycotoxin citrinin reduction by Monascus aurantiacus Li AS3.4384 during liquid-state fermentation

Abstract: Monascus can produce many beneficial metabolites; however, it can simultaneously also produce citrinin, which seriously limits its application. Therefore, reducing the production of citrinin is of great interest. Herein, Monascus aurantiacus Li AS3.4384 (MAL) was used to optimize the liquid-state fermentation process and investigate the effects of genistein and other flavonoids on citrinin, pigments, and biomass of MAL. Results showed that citrinin decreased by 80%, pigments and biomass increased by approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
3
15
1
1
Order By: Relevance
“…It was predicted that the most effective flavonoid compounds in inhibiting the production of citrinin toxin should have a chemical structure including a benzyne ring at the position of C3 and have OH groups at positions C5, C4 and C7, which was consistent with the structure of rutin and catechin, where OH groups are located at position C5, C4 ' and C7 and were able to reduce the production of citrinin by up to 80%. This result disagreed with Wang et al (2020). In the current study, M. purpureus was able to grow and produced more pigment than the control without phenolic compounds.…”
Section: Types Of Phenolic Compounds In Inhibition Of Fungal Growthcontrasting
confidence: 98%
See 3 more Smart Citations
“…It was predicted that the most effective flavonoid compounds in inhibiting the production of citrinin toxin should have a chemical structure including a benzyne ring at the position of C3 and have OH groups at positions C5, C4 and C7, which was consistent with the structure of rutin and catechin, where OH groups are located at position C5, C4 ' and C7 and were able to reduce the production of citrinin by up to 80%. This result disagreed with Wang et al (2020). In the current study, M. purpureus was able to grow and produced more pigment than the control without phenolic compounds.…”
Section: Types Of Phenolic Compounds In Inhibition Of Fungal Growthcontrasting
confidence: 98%
“…In the current study, rutin and catechin reduced the production of citrinin by 81.12% and 92.02%, respectively. These results were consistent with Wang et al (2020), who reported that the flavonoid compounds apigenin and kaempferol were able to reduce the production of citrinin by MALA, by 50%, luteolin and quercetin were able to reduce the production of citrinin by 60-67%, while genistein was the most potent by reducing the production of citrinin by up to 80%. It was predicted that the most effective flavonoid compounds in inhibiting the production of citrinin toxin should have a chemical structure including a benzyne ring at the position of C3 and have OH groups at positions C5, C4 and C7, which was consistent with the structure of rutin and catechin, where OH groups are located at position C5, C4 ' and C7 and were able to reduce the production of citrinin by up to 80%.…”
Section: Types Of Phenolic Compounds In Inhibition Of Fungal Growthsupporting
confidence: 92%
See 2 more Smart Citations
“…A number of studies have reported a wide range of health beneficial pigment compounds present in MPs [21][22][23][24]. The production of toxic secondary metabolites (e.g., citrinin, a nephrotoxic mycotoxin) by Monascus species has also been reported [25][26][27]. However, a review of the literature shows that, in most research on this topic, extracted pigment mixtures rather than individual compounds, are used.…”
Section: Introductionmentioning
confidence: 99%